Developed Spreadsheet-based System for Statistical Analysis of Grade 12 Learners - Salvador, Miguel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of a developed spreadsheet-based system in improving the statistical analysis skills of Grade 12 learners at Tabuk City National High School. Anchored on Piaget’s constructivist theory, the study investigated whether a spreadsheet-based learning environment could enhance learners’ ability to compute, organize, interpret, and present statistical data. A true-experimental pretest-posttest control group design was employed involving 172 Grade 12 learners enrolled in Practical Research 2 from the Home Economics and Accountancy, Business, and Management strands. Researcher-developed pretest and posttest instruments were used to assess statistical analysis proficiency, and data were analyzed using descriptive and inferential statistics. Findings revealed that both Microsoft Excel add-ins and the developed spreadsheet-based system significantly improved learners’ statistical analysis performance. The Microsoft Excel add-ins group improved from a mean score of 15.77 to 85.01, while the developed spreadsheet-based system group improved from 14.15 to 90.13. Statistical tests confirmed significant differences between pretest and posttest scores in both groups. Moreover, the developed spreadsheet-based system demonstrated significantly higher posttest performance than Microsoft Excel add-ins, indicating greater effectiveness in supporting statistical computations, data organization, and presentation. The results suggest that customized spreadsheet-based technologies can effectively address learners’ difficulties in statistical analysis and strengthen research-related competencies. The study concludes that integrating accessible and user-friendly digital tools into research instruction can substantially improve learners’ statistical analysis skills. It recommends the adoption and continuous enhancement of spreadsheet-based instructional technologies to support statistics and research education. This study supports Sustainable Development Goal (SDG) 4: Quality Education and SDG 9: Industry, Innovation and Infrastructure by promoting innovative and accessible technologies that enhance learning outcomes. Its sustainability contribution lies in strengthening educational practices, improving digital learning opportunities, and providing cost-effective tools that support research competence among learners, particularly in resource-constrained settings.